Influencer Marketing and Purchase Intention: The Mediating Role of Trust - Evrianti, Hesti; Wanti, Sri; Asriadi; Wulandari, Poppy (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Digitalization had transformed consumption patterns, positioning influencer marketing as a dominant strategy in contemporary business. Social media influencers significantly enhanced brand awareness and purchase intention, particularly among students as active technology users. However, their impact was mediated by trust, which strengthened consumer responses to marketing messages. Thus, examining trust as a mediating variable between influencer marketing, brand awareness, and purchase intention was essential to advance marketing knowledge within the student market segment.Purpose: This study aims to examine the influence of influencer marketing on brand awareness and purchase intention, emphasizing the mediating role of trust. While influencer marketing is recognized as a driver of consumer decisions, its impact is often indirect, shaped by consumer trust. Prior studies have overlooked this mediating factor, particularly within the student market segment. Addressing this gap, the research provides new insights into digital marketing by highlighting trust as a critical determinant of effectiveness.Design/Methodology/Approach: This study employed a quantitative research design at Tadulako University, Palu, Indonesia, from February to October 2024. Data were collected through a structured questionnaire distributed to 86 postgraduate students, determined via the Slovin formula from a population of 630. The instrument, validated by expert review and pilot testing, used a five-point Likert scale. Data analysis utilized descriptive statistics and path analysis with SmartPLS 4 to examine causal relationships and ensure validity and reliability.Finding/Result: The results demonstrate that influencer marketing significantly enhances brand awareness, purchase intention, and trust among students. Trust itself positively influences both brand awareness and purchase intention, while also serving as a significant mediator between influencer marketing and these outcomes. Path analysis confirms all hypotheses, underscoring the central role of trust in strengthening consumer perceptions and decisions. These findings highlight that influencer marketing effectiveness depends not only on brand exposure but also on building sustainable trust-based relationships.Conclusion: This study concludes that influencer marketing significantly enhances brand awareness and purchase intention among graduate students, with trust acting as a pivotal mediating factor. Trust reduces perceived risks and reinforces consumer confidence, thereby amplifying marketing effectiveness. The study contributes novel insights by positioning trust as a central mechanism in digital marketing strategies. However, due to the limited sample size, findings should be interpreted cautiously and further validated across broader contexts and product categories.Originality/State of the art: This research contributes to the existing literature by emphasizing the mediating role of trust in influencer marketing's effects on graduate students, providing insights for marketers targeting this demographic in the context of mobile phone purchases. Keywords: influencer marketing, brand awareness, purchase intention, consumer decisions, digital marketing